PREPARATIVE ISOLATION AND PURIFICATION OF THREE GLYCINE-CONJUGATED CHOLIC ACIDS FROM PULVIS FELLIS SUIS BY HIGH-SPEED COUNTERCURRENT CHROMATOGRAPHY COUPLED WITH ELSD DETECTION - He, Jiao (2012)
Coupled with evaporative light scattering detection, a high-speed counter-current chromatography (HSCCC) method was developed for preparative isolation and purification of three glycine-conjugated cholic acids, glycochenodeoxycholic acid (GCDCA), glycohyodeoxycholic acid (GHDCA) and glycohyocholic acid (GHCA) from Pulvis Fellis Suis (Pig gallbladder bile) for the first time. The separation was performed with a two-phase solvent system consisted of chloroform-methanol-water-acetic acid (65:30:10:1.5, v/v/v/v) by eluting the lower phase in the head-to-tail elution mode. The revolution speed of the separation column, flow rate of the mobile phase and separation temperature were 800 rpm, 2 ml/min and 25 °C, respectively. In a single operation, 33 mg of GCDCA, 38 mg of GHDCA and 23 mg of GHCA were obtained from 200 mg of crude extract with the purity of 95.65%, 96.72% and 96.63%, respectively, in one step separation. The HSCCC fractions were analyzed by high-performance liquid chromatography (HPLC) and the structures of the three glycine-conjugated cholic acids were identified by ESI-MS, (1)H NMR and (13)C NMR.